Peningkatan Minat Belajar dan Minat Baca Siswa melalui Media E-Learning dan E-Library untuk Mendukung Program Gerakan Literasi Sekolah (GLS) pada Sekolah dan Madrasah di Kab/Kota Blitar Tahun 2020 - Fanani, Moh. Zainal; Surahmat, Surahmat; Prasetyo, Hendra Ade; Puji Hastuti, Maya Dwi; Rohim, Bima Nur Fadhilatur; Abdullah, Ahmad Afif; Alfarizi, Akhmad Salman (UAS PRESS, 2021)
The civilization of an advanced nation is built from a culture of science and literacy that develops continuously between generations. Along with the development of knowledge and technology, especially in the digital field, literacy culture, including digital literacy, is one of the important aspects that must be implemented in schools. Literacy culture includes literacy, numeracy/mathematical literacy, scientific literacy, information and communication technology literacy, financial literacy, and cultural literacy and citizenship. In connection with the above, the research-based community service team of IAIN Kediri provided training and assistance with the theme